Analisis Pengaruh Pembiayaan Murabahah dan Musyarakah Terhadap Profitabilitas Bank Syariah Di Indonesia Periode 2019-2021 - Aminulloh, Ali; Khoirun Khasanah, Nur Laila; Zaytun, Nurul (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
Banking is one of the Islamic financial instruments that plays an important role in developing the people's economy through various types of financing based on sharia principles. Murabaha and musyarakah financing are types of financing in Islamic banks which are a favorite among the public. The author wants to reveal how big the contribution made by the two financing is to the profitability of Islamic banks in Indonesia. The purpose of this research is to determine the significant effect of murabaha and musyarakah financing, both partially and simultaneously on the profitability of Islamic banks in Indonesia in the 2019-2021 period. The methodology used is a descriptive quantitative approach with data analysis techniques using multiple linear regression. The data collection technique uses documentation techniques where the data is oriented to secondary data which will then be processed with SPSS 25 software. The results of this study found that: the significance level test was 0.000 and the ttest result was 4.450. So the significance level is 0.000 <0.05 and the tcount > ttable (4.450 > 2.035) means that Ha is accepted and Ho is rejected. The results of the multiple linear regression test show a number of 0.228 (positive value) for the Murabahah variable so that it can be said that Murabahah financing is positively related to profitability, the test results at a significance level of 0.000 and the t-test results are 4.568. Then the significance level is 0.000 <0.05 and the tcount > ttable (4.568 > 2.035) means that Ha is accepted and Ho is rejected and the results of the multiple linear regression test show the number 0.228 (positive value) for the Murabahah variable so that it can be said that Murabahah financing is positively related with profitability. The results of the significance level test were 0.000 and the t-count test results were 10.591. So the significance level is 0.000 <0.05 and the tcount > ttable (10.591 > 3.275) means that Ha is accepted and Ho is rejected. This states that murabaha and musyarakah financing have a significant effect on profitability.